Collective action to secure land management rights for poor communities - Siagian, Y.; Neldysavrino (Center for International Forestry Research, 2007)
The brief illustrates two communities’ efforts through collective action to secure property rights over their land. As conflict over natural resources and the need for sufficient farm land continue to increase, both men’s and women’s groups tried to negotiate their rights to manage natural resources to maintain their livelihoods. The groups also tried various governmental schemes and other approaches to secure their rights over land. The brief also describes lessons derived from the experience of implementing Participatory Action Research in catalyzing collective action among community groups in the two villages (Sungai Telang and Lubuk Kambing) in Jambi Province, Sumatra.